Does the anteromedial portal provide clinical superiority compared to the transtibial portal in anterior cruciate ligament reconstruction in nonprofessional athletes in short-term follow-up? - TASDEMIR, Zeki; GULABI, Deniz; SAGLAM, Fevzi; OZAL, Safiye Tokgoz; Elmali, NURZAT; ELMALI, NURZAT (My University, 2015)
Objective: Two drilling techniques of the femoral tunnel are commonly used in anterior cruciate ligament (ACL) reconstruction: through the transtibial (TT) portal or through the anteromedial (AM) portal. The aim of the present study is to investigate the radiological and clinical outcomes of arthroscopic single-bundle ACL reconstruction using AM and TT portal techniques for drilling the femoral tunnel in nonprofessional athletes. Methods: A retrospective review was made of 44 nonprofessional athletes undergoing ACL reconstruction using AM and TT techniques between 2011-2013. The femoral tunnel clock position on axial magnetic resonance imaging (MRI) and the anterior-posterior position of the tibial tunnel on sagittal-cut MRI scan were measured. Radiological femoral tunnel and tibial tunnel anterior-posterior inclination angles were assessed. At final follow-up, the Lachman test and pivot-shift test were used in the evaluation of the anterior-posterior stability of the knee and the rotational stability of the knee. For clinical and functional evaluation, the modified Cincinnati knee grading system, Lysholm knee scoring scale, and International Knee Documentation Committee (IKDC) form were used. Results: No statistically significant difference was determined between the groups in terms of patient age, follow-up period, gender, and affected side distribution. There were 6 outliers in the TT group due to the clock face position. The mean femoral tunnel inclination angle was 31.07°±8.44° in the AM group and 19.02°±8.93° in the TT group. The tibial tunnel inclination angle was 21.08°±5.42° in the TT group and 16.58°±7.02° in the AM group. A statistically significant difference was determined between the 2 groups. No statistically significant difference was observed between the 2 groups in terms of Lachman test, pivot-shift test, Lysholm score, IKDC score, and modified Cincinnati score results. Conclusion: The AM technique has no clinical superiority compared to the TT technique in ACL reconstruction in nonprofessional athletes.